Antifungal properties of (2S, 4R)-Ketoconazole sulfonamide analogs - Blass, Benjamin E.; Puri, Sumant; Sharma, Rishabh; Day, Brian M. (Frontiers in Drug Discovery, 2022)
Invasive candidiasis remains a significant health concern, as it is associated with a high mortality risk. In addition, the risk of infection is significantly elevated in immunocompromised patients such as those with HIV, cancer, or those taking immunosuppressive drugs as a result of organ transplantation. The majority of these cases are caused by C. albicans, and C. glabrata is the second most common cause. These infections are typically treated using approved antifungal agents, but the rise of drug-resistant fungi is a serious concern. As part of our on-going effort to identify novel antifungal agents, we have studied the in vitro antifungal properties of a series of sulfonamide analogs of (2S, 4R)-Ketoconazole. Herein we report on the in vitro activity against the key fungal pathogens C. albicans, and C. glabrata.